2020
DOI: 10.1002/ep.13429
|View full text |Cite
|
Sign up to set email alerts
|

Practice on treating pharmaceutical compounds (antibiotics) present in wastewater using biosorption techniques with different biowaste compounds. A review

Abstract: Pharmaceutical and Public Care Products (PPCP) enable a healthy lifestyle for individuals, but the non-metabolized components get released to the environment, which creates an adverse impact on the environment, especially the aquatic ecosystem. PPCP is considered a secondary pollutant, but it has the potential to become a primary pollutant due to its bioaccumulation and lasting detrimental effects. Primary wastewater treatments like coagulation, sedimentation, and flocculation are not suitable for the exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 91 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…It is a process typically independent of energy, employing dead or waste biomass of low cost. Most biological waste materials can be efficiently and directly used as readily available biosorbents for removal of organic and inorganic pollutants and radionuclides from e.g., residual waters (de Freitas et al, 2019;Silva et al, 2019;Beni and Esmaeili, 2020;Fawzy and Gomaa, 2020;Magesh et al, 2020;Ubando et al, 2021; Table 1). Biosorption of pollutants on biosorbents usually includes several mechanisms based on the presence of appropriate functional groups (e.g., hydroxyl, carboxyl, amino, phosphate, sulfate, amide, imidazole, thiol, acetamide, etc.…”
Section: Biosorbentsmentioning
confidence: 99%
“…It is a process typically independent of energy, employing dead or waste biomass of low cost. Most biological waste materials can be efficiently and directly used as readily available biosorbents for removal of organic and inorganic pollutants and radionuclides from e.g., residual waters (de Freitas et al, 2019;Silva et al, 2019;Beni and Esmaeili, 2020;Fawzy and Gomaa, 2020;Magesh et al, 2020;Ubando et al, 2021; Table 1). Biosorption of pollutants on biosorbents usually includes several mechanisms based on the presence of appropriate functional groups (e.g., hydroxyl, carboxyl, amino, phosphate, sulfate, amide, imidazole, thiol, acetamide, etc.…”
Section: Biosorbentsmentioning
confidence: 99%
“…Studies have shown that over 80% of amoxicillin is excreted in human urine within the first two hours after ingestion, with a portion of its active form not completely metabolized. This results in its presence in effluents from wastewater treatment plants at concentrations ranging from 170 to 1270 ng/L [6][7][8], in surface waters between 120 and 200 ng/L [9], and in hospital effluents, reaching up to 900 ng/L in Australia [10].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of adsorbents is crucial to achieving the highest removal efficiency by adsorption. Different adsorbents, such as clay minerals [26], graphene-based nanocomposites [27], activated carbon [28], biomass [29], and hydroxyapatites [30,31] have been recently exploited for the removal of antibiotics from water, as indicated in the pertinent literature.…”
Section: Introductionmentioning
confidence: 99%